Peran Kepemilikan Keluarga Dalam Memoderasi Pengaruh Fraud Pentagon Terhadap Kecurangan Laporan Keuangan - larasati, ressa; chariri, anis (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
Detecting potential financial reporting fraud in the IDX-listed real estate and property firms between 2019 and 2023, this study applies the Fraud Pentagon Theory. Five components of fraud are identified by the model: leverage as a proxy for pressure, poor monitoring as a proxy for opportunity, rationalization as a proxy for auditor changes, capacity as a proxy for board changes, and hubris as a proxy for CEO duality. Family ownership is employed as a moderating variable to ascertain if it strengthens or weakens the correlation between financial statement fraud and the Fraud Pentagon components. SPSS version 25 was utilized to perform the logistic regression analysis in this quantitative investigation. The 58 businesses that comprise the sample were chosen through the use of purposeful sampling. The results show that while poor monitoring and auditor changes have a considerable favorable influence on financial statement fraud, leverage, board changes, and CEO duality have no discernible effect. Furthermore, family ownership cannot reduce the impact of other factors on fraud; it can only reduce the association between board changes and financial statement fraud. These results suggest that family ownership is not always effective in preventing financial statement fraud, especially in companies with high leverage or weak internal monitoring. This study recommends that future research consider other relevant variables for analyzing financial statement fraud. Keywords: Fraud Pentagon, Financial Statement Fraud, Family Ownership